Our daily bread and climate change – students’ awareness of the climate change and their contribution to mitigation through dietary habits - Tolić Mandić, Iva; Markanović, Dragana; Tišma, Sanja (Crisis Management Days, 2024)
Introduction Climate change is one of the most serious risks today’s society is facing. According to the European Commission and European Parliament (2008), climate change is the second serious problem in the world. Research conducted by European Commission and European Parliament showed that in 2008, one-third of Europeans were aware that climate change is serious problem, while in 2021, 93% of people considered climate change a serious problem. Since one of the largest sources of greenhouse gases (GHG) emissions is agriculture and food system as a whole, a change in food consumption patterns could positively affect climate change mitigation. The results of previous researchers have shown that animal-based products – meat and dairy, as well as ultra-processed food are associated with highest GHG emissions (Lochman, 2023, da Cruz, et al., 2024), while plant-based food has lower GHG intensity (Poore & Nemecek, 2018). The importance of effect of food consumption was recognised by Jürkenbeck, et al. (2021), who analysed the awareness of climate change of young population in Germany and showed that half of the young generation is highly aware of climate change, while minority think that climate change does not exist. The results of the research also showed that young people aware of the climate change choose more climate sustainable nutrition. The main goal of this research was to analyse the awareness of students in Croatia on the importance of climate change and awareness of their possibility to contribute to climate change mitigation through change of their consumption habits. Methodology The research was conducted in the form of questionnaire and it included 20 students. The questionnaire was divided into three parts. First part of the questionnaire analysed personal attitudes towards climate change. In the second and third part, students have been asked to choose the most climate and environmentally sustainable foods and practices. One of the choices was also the answer “I do not know”, to exclude the possibility of guessing the correct answer. Results The results of the research showed that students are aware of the importance of climate change and the role of European countries, including Croatia, in climate change. Also, students are aware that people are not familiar with climate change and they believe that there is a need to educate children in school about climate change. On the other hand, although students are aware that climate change is a serious problem, they are not aware of how it occurs and that the food that is produced, stored, transported, prepared and finally consumed affects climate change. The results showed that most of the students cannot recognize the most sustainable practices in food production, distribution, packaging and consumption. Moreover, the students’ knowledge about impact of food on the environment is weak and there is a need for further education about individual contribution to climate change mitigation.